2008
DOI: 10.4161/cbt.7.7.6099
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone reduces tumor recurrence and metastasis after pancreatic tumor resection in SCID mice

Abstract: Conclusions: DEX has a profound influence on the malignant phenotype of PDAC tumor cells in vitro in terms of inhibition of invasiveness and pro-inflammatory signaling. This was approved in vivo by reduced metastasizing capacity and reduced size of local tumor recurrence. Therefore, DEX-treatment appears to be an interesting therapeutical option in an adjuvant setting after pancreatic cancer resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Surgery causes inevitable inflammatory response in tumor microenvironment; therefore, GCs might be beneficial in reducing acute phase inflammatory reaction, even though GCs may possibly suppress immune response against cancer. One study has shown beneficial results of DEX treatment for the host after resection of pancreatic cancer (25). DEX was found to reduce metastasis and size of local tumor recurrence (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery causes inevitable inflammatory response in tumor microenvironment; therefore, GCs might be beneficial in reducing acute phase inflammatory reaction, even though GCs may possibly suppress immune response against cancer. One study has shown beneficial results of DEX treatment for the host after resection of pancreatic cancer (25). DEX was found to reduce metastasis and size of local tumor recurrence (25).…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown beneficial results of DEX treatment for the host after resection of pancreatic cancer (25). DEX was found to reduce metastasis and size of local tumor recurrence (25). Therefore, to maximize the efficacy of cancer therapy, more specific understanding of the cancer cells themselves and the tumor microenvironment is necessary, because the effect of DEX on solid tumor can be still double-edged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this steroid results in a profound influence on the malignant phenotype but it is not clear whether this effect is due to direct action or inhibition of proinflammatory singals [45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hMSH2 and hPMS1 could be immunogenic antigens in patients with pancreatic adenocarcinoma. Additionally Egberts et al showed that dexamethasone treatment had profound influence of pancreatic duct adenocarcinoma cells in vitro in terms of inhibition of invasiveness and activation of NFκB which was approved in vivo by reduced metastasing capability and reduced size of local tumour recurrence in an experimental model of pancreatic cancer[15]. These observations indicate that the link between malignancy and inflammatory myopathy relates possibly to the expression of common autoantigens between cancer tissue and muscle tissue in some patients with polymyositis.…”
Section: Discussionmentioning
confidence: 99%